The Influence Of Transformational Leadership And Work Environment On Satisfaction Work That Impact Employee Performance (Study on employees of PT Astra International Tbk Makassar City) - Muhammad Ainul Yakin Rahim; Kusdi Raharjo; Gunawan Eko Nurtjahjono (Jurnal Mamangan, 2024)
This research is motivated by the decline in employee job satisfaction and performance that has occurred in the last three years at PT Astra International Tbk Makassar City. This study aims to analyze the influence of transformational leadership and work environment on employee performance with job satisfaction as a mediating variable. This study uses an explanatory research method with a quantitative approach, where primary data were collected through distributing questionnaires to 112 employees and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results show that transformational leadership and work environment have a significant effect on job satisfaction. Furthermore, job satisfaction is proven to have a positive and significant effect on performance. The main findings reveal that transformational leadership does not have a significant direct effect on performance, but its effect is fully mediated by job satisfaction. Conversely, the work environment has a significant direct effect on job satisfaction and employee performance. In conclusion, efforts to improve employee performance can be carried out effectively through improving transformational leadership styles and creating a conducive work environment to increase job satisfaction, which in turn has a positive impact on performance